The burden of skeletal-related events in four Latin American countries: Argentina, Brazil, Colombia, and Mexico. (1st January 2021) - Garcia Perlaza, Javier; Aziziyeh, Rima; Zhou, Anna; De Sousa Barbosa, Vitor; Amaya, Jenny; Caporale, Joaquin; Alva, Monica Elena; Forero, Juan; Tanaka, Straus; Suri, Gaurav; Garcia, David
Abstract: Aim: Skeletal-related events (SREs) are major bone complications that frequently occur in patients with solid tumors (ST) and bone metastases, and in patients with multiple myeloma (MM). SREs include pathological fracture, spinal cord compression, radiation to bone, and surgery to bone. Limited data are available regarding the burden of SREs in Latin America. We built an economic model to quantify the current and future economic burden of SREs among adults in four Latin American countries: Argentina, Brazil, Colombia, and Mexico. Methods: A comprehensive literature review with a systematic search strategy was conducted to parameterize the economic burden of illness (BOI) model. Economic analyses were conducted using a prevalence-based model. Aggregate SRE costs obtained from country-specific sources were used. We also included patient productivity losses. Costs were expressed in 2020 USD for the total annual burden, annual burden per 1, 000 at risk, and projected five-year burden. Results: The estimated total number of SREs was 251, 503 in 2020, amounting to a total annual cost of USD 1.4 billion. The total projected five-year cost was USD 6.9 billion. Annual costs were highest in Brazil (USD 779.1 million), followed by Mexico (USD 281.8 million), Argentina (USD 174.6 million), and Colombia (USD 120.1 million). The average financial burden per 1, 000 at risk was greatest in Brazil (USD 3.6 million), followed by Mexico (USD 3.4 million), Colombia (USD 2.9 million), and Argentina (USD 2.7 million). Conclusion: Despite recommendations by medical societies for the use of bone-targeted agents in patients with solid tumors and bone metastasis or with multiple myeloma and bone lesions, a large proportion of patients at risk of experiencing SREs are not treated. Early detection of bone metastases and SREs and the use of the most effective preventative treatments are needed to decrease the clinical and economic burden of SREs in Latin America.